Benefits of consuming Coffea arabica - Maria Crina Isac (Acta et Commentationes Exact and Natural Sciences, 2025)
Coffee is one of the most important tropical crops in developing countries, but has been relatively little studied from a nutritional and agricultural management perspective. Arabica coffee (Coffea arabica), which is part of the genus Coffea of the Rubiaceae family, is the most widely cultivated species worldwide, accounting for over 75% of total coffee production.This plant contains a complex combination of chemical compounds with beneficial effects on health. Over time, various parts of coffee have been used in traditional medicine, and modern research has confirmed its antioxidant, antiinflammatory and antimicrobial properties. Coffee consumption is associated with benefits for the nervous system, metabolism and cardiovascular health, with preventive potential in diseases such as diabetes and neurodegenerative disorders.This paper aims to explore the positive effects of Arabica coffee on health, highlighting the importance of its bioactive compounds